Polymerization of 2-hydroxyethyl methacrylate by hydro/solvothermal technique in presence of nanographene: electrical and thermal degradation characterization - Biryan, Fatih; Acikses, Aslisah; Demirelli, Kadir (Springer, 2021)
Nanocomposites of poly(2-hydroxyethyl methacrylate) (PHEMA) loaded with 1.7 mass%, 6.5 mass% and 9.0 mass% nanographene were prepared by hydro/solvothermal technique. The main peaks of the nanographene and amorphous polymer structure were revealed by X-ray diffraction (XRD) analysis. Nanocomposites were characterized by SEM, DSC and TGA techniques. The dielectric constant (epsilon MODIFIER LETTER PRIME), the dielectric loss factor (epsilon), the loss tangent (tan delta) and the conductivity (sigma(ac)) were measured using a dielectric analyzer in a frequency range from 100 Hz to 2 kHz. Also, current (I)-voltage (V) measurements were carried out. It is well known that nanocomposite formation causes an improvement of many properties for a polymer, providing enhanced properties such as conductivity and thermal stability. This investigation was done to understand whether the presence of nanographene causes changes in the degradation pathway of poly(HEMA) prepared by hydro/solvothermal technique. For this aim, pure poly(HEMA) and nanocomposites were heated from room temperature to 500 degrees C. The characterization of degradation products for the cold ring fractions (CRFs) and trapped at - 196 degrees C (in liquid nitrogen) was investigated by means of FT-IR,H-1,C-13-NMR spectroscopic and GC-MS techniques. The FT-IR, NMR and GC-MS data showed that depolymerization corresponding to monomer (2-hydroxyethyl methacrylate) was the most important product trapped at CRF and - 196 degrees C in the thermal degradation of nanocomposites. As the nanographene loading increased in composite systems, the rate of depolymerization of poly(HEMA) increased compared to pure poly(HEMA). The nanographene particles in the composite systems acted as a mass barrier that retards the escape of the volatile products
Keywords: Hydro; solvothermal; HEMA; Dielectric properties; Degradation; Composite